2012
DOI: 10.1001/jama.2012.12505
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vitamin D3Supplementation on Upper Respiratory Tract Infections in Healthy Adults

Abstract: anzctr.org.au Identifier: ACTRN12609000486224.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
163
3
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(177 citation statements)
references
References 28 publications
4
163
3
3
Order By: Relevance
“…We recognize that with well .4000 genes directly or indirectly regulated by vitamin D and its metabolites, additional mechanisms of regulation beyond those examined in this article are also likely to contribute to this differential activity. Carlberg et al (38) The benefits of aggressive vitamin D supplementation in vivo have recently become controversial (2,(39)(40)(41)(42). A commonly cited epidemiologic rationale for such supplementation is to enhance protective immune capacity and to decrease inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…We recognize that with well .4000 genes directly or indirectly regulated by vitamin D and its metabolites, additional mechanisms of regulation beyond those examined in this article are also likely to contribute to this differential activity. Carlberg et al (38) The benefits of aggressive vitamin D supplementation in vivo have recently become controversial (2,(39)(40)(41)(42). A commonly cited epidemiologic rationale for such supplementation is to enhance protective immune capacity and to decrease inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The degree of gargling Other interventions A variety of other interventions have been studied for the prevention of the common cold. Studies of exercise, 41 garlic 42,43 and homeopathy 44−46 showed unclear evidence of benefit, whereas those of vitamin D 48,49 and echinacea 50 showed no evidence of benefit. Vitamin C 47 may provide some benefit in people under physical stress (e.g., marathon runners or soldiers in subarctic environments), but no meaningful benefit has been shown for the average patient.…”
Section: Garglingmentioning
confidence: 99%
“…A growing literature (1)(2)(3) suggests that vitamin D may be associated with reduced mortality (overall (4) and hospital-associated (5) ), incidence of cancer (6)(7)(8)(9)(10)(11)(12)(13) , CVD (14,15) , diabetes (16) , fractures (17,18) and ageing-related functional limitations (19) , although some studies find an unclear relationship (20,21) or a harmful association with disease (22) . Randomized controlled trials are underway to examine the potential role of vitamin D in the prevention of multiple diseases, including cancer, CVD and diabetes (20,23) .…”
Section: Introductionmentioning
confidence: 99%